Faktor-Faktor yang Mempengaruhi Minat Berinvestasi Saham: (Studi Pada Mahasiswa Jurusan Akuntansi Universitas Negeri Gorontalo) - Fadhilah Nur Aini Salehe; Hapsawati Taan; Usman Usman (Al-Buhuts, 2023)
This study aims to determine the factors that influence interest in stock investment in students of the Accounting Department, State University of Gorontalo through the factors of investment knowledge and information technology. This type of research uses a quantitative approach. The population in this study were active S1 students majoring in Accounting at Gorontalo State University in 2019-2020. The sampling technique in this study used the slovin formula with a total of 99 people. The type of data used in this study is primary data, namely data obtained directly from the respondents. The data analysis technique in this study is multiple linear regression. The data collection method was carried out by distributing questionnaires to active S1 students in the Department of Accounting. The results of this study are that investment knowledge and information technology have a positive and significant effect on interest in investing in shares of students of the Accounting Department, State University of Gorontalo